Cultural Competency and Rural Disorder in PNG Health Promotion. Issue 4 (2nd October 2018) - Andersen, Barbara
ABSTRACT: Health workers in Papua New Guinea strongly emphasise their duty to provide services to the country's rural majority. Trained to see rural communities as lacking modern discipline and order, they worry that rural people will resist, perhaps with violence, if health workers fail to 'show respect for culture'. Examining cultural improvisation among nursing students on a rural experience practicum in the Eastern Highlands, I show how students and teachers tried to craft culturally respectful health education. However, when difficulties emerged, local people were described as unable or unwilling to harim tok (understand, heed or follow instructions). The capacity to follow instructions, cultivated through education and Christian faith, was cast as incompatible with Highlands culture. Rural health promotion activities, when they fail to foment major transformation, can help reproduce the ideological construction of the people of the hauslain (village, hamlet) as emotionally volatile and ungovernable.